Primary tooth length determination in direct digital radiography: An in vivo study - Santos-Pinto, Lourdes [UNESP]; Cordeiro, Rita De Cássia Loiola [UNESP]; Zuanon, Angela Cristina Cilense [UNESP]; Basso, Maria Daniela; Gonçalves, Marcela Almeida (My University, 2007)
Purpose: The purpose of this in vivo study was to compare the accuracy of primary incisor length determined by direct digital radiography (straight-line measurement and grid superimposition) and measurement of the actual tooth length. Methods: Twenty-two primary maxillary incisors that required extractions were selected from 3- to 5-year-old children. The teeth were radiographed with an intraoral sensor using the long cone technique and a sensor holder (30-cm focus-to-sensor distance). The exposure time was 0.3 seconds. Tooth length was estimated by using straight-line and grid measurements provided by the distance measurement feature of the Computed Dental Radiography digital dental imaging system. The actual tooth length was obtained by measuring the extracted tooth with a digital caliper. Data were analyzed statistically by Pearson's correlation coefficient and a paired t test. Results: There were statistically significant differences (P=.007) between the 2 measurement techniques and between the actual tooth lengths and grid measurements. There was no statistically significant difference (P=38) between straight-line measurements and actual tooth lengths, showing that the straight-line measurements were more accurate. Underestimation of the actual tooth length, however, occurred in 45% of the straight-line measurements and in 73% of the grid measurements. Conclusion: It is possible to determine primary tooth length in digital radiographs using onscreen measurements with a reasonable degree of accuracy.
Keywords: Computer-assisted imaging processing; Diagnostic imaging; Digital radiography; Primary tooth; Tooth length